2020
DOI: 10.3390/met10040517
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Simulation of Non-Metallic Inclusion Aggregation in a Fully Resolved Bubble Swarm in Liquid Steel

Abstract: Removing inclusions from the melt is an important task in metallurgy with critical impact on the quality of the final alloy. Processes employed with this purpose, such as flotation, crucially depend on the particle size. For small inclusions, the aggregation kinetics constitute the bottleneck and, hence, determine the efficiency of the entire process. If particles smaller than all flow scales are considered, the flow can locally be replaced by a plane shear flow. In this contribution, particle interactions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Before discussing on the population aggregation dynamics, it is useful to investigate how primary particles aggregate depending on their surface potentials. In fact, the complex interplay between hydrodynamic and colloidal interactions determines the aggregation efficiency of colloidal particles, which, especially when starting from monomeric conditions, strongly affects the early stage of the aggregation process.…”
Section: Resultsmentioning
confidence: 99%
“…Before discussing on the population aggregation dynamics, it is useful to investigate how primary particles aggregate depending on their surface potentials. In fact, the complex interplay between hydrodynamic and colloidal interactions determines the aggregation efficiency of colloidal particles, which, especially when starting from monomeric conditions, strongly affects the early stage of the aggregation process.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers [36,37] have found that MgO-Al 2 O 3 has a high potential for acting as a TiN nucleation site because of the low disregistry. The existing form of Al 2 O 3 inclusions was Al 2 O 3 with a TiN layer in this study, which means that the formation of an inclusion of MgO-Al 2 O 3 surrounded by a TiN layer was from an inclusion of the Al 2 O 3 surrounded by a TiN layer, as shown in Equations ( 9)- (11). With regard to the MgO-Al…”
Section: Evolution Mechanism Of Oxide Inclusions During the Esr Processmentioning
confidence: 58%
“…The obtained oxide inclusion in the electrode was Al 10), and the (MgO) in the inclusions appeared. Combining Equations ( 9) and (10), we can find that the (MgO) in the slag transformed into (MgO) in the inclusions through (Al 2 O 3 ), as shown in Equation (11), and the Gibbs energy was 0 [35]. Therefore, the inclusions of Al 2 O 3 transformed to a spinel solid solution.…”
Section: Evolution Mechanism Of Oxide Inclusions During the Esr Processmentioning
confidence: 94%
See 1 more Smart Citation
“…Complex dynamics arise in particle interactions at finite Reynolds number, even at values down to Re ∼ 10 −2 [53,54], that may have a significant impact on aggregate behaviour. The LBM as used in this research is well suited for finite Reynolds simulations, unlike SD.…”
Section: Discussionmentioning
confidence: 99%